Titanium K-edge XAS study on local structure of Pb1-xCaxTiO3 ferroelectric ceramics - Mesquita, Alexandre [UNESP]; Estrada, Flávia Regina; Mastelaro, Valmor Roberto; Eiras, José Antonio; Garcia, Ducinei (Trans Tech Publications Ltd, 2014)
In order to characterize the local structure of Pb1-xCaxTiO3 (PCT) samples, Ti K-edge XANES measurements were performed and showed that Ca incorporation to PbTiO3 structure leads to a decreasing of local distortion of Ti atoms in relation to oxygen atoms at the TiO6 octahedra. Moreover, according to EXAFS measurements, the local structure around Ti atoms exhibits tetragonal symmetry with P4mm space group for samples with x <= 0.475, whereas orthorhombic symmetry with Pbnm space group was observed for x equals to 0.50 and 0.55.
Keywords: Pb1-xCaxTiO3; Structural phase transition; XANES; EXAFS